Pengaruh Inflasi, Nilai Tukar, dan Pertumbuhan Ekonomi terhadap Indeks Harga Saham Jakarta Islamic Index Tahun 2006-2020 - Sania Fasya; Dewi Rahmi; Westi Riani (Bandung Conference Series: Economics Studies, 2022)
Abstract. From a macro perspective, investment is one of the components of final demand, which is an indicator of internal balance in the product market equilibrium situation. On the other hand, micro investment reflects the business world because the source of investment is the business world. The development of the Islamic capital market in Indonesia is increasingly lively with the birth of the Jakarta Islamic Index (JII). There are factors that influence Jakarta Islamic Index, namely macroeconomic variables.The purpose of this study is to determine the effect of inflation, exchange rates, and economic growth on the Jakarta Islamic Index stock price index.The data used in this study is secondary data. The independent variables include inflation, exchange rates, and economic growth. The dependent variable is the Jakarta Islamic Index. The dependent variable is the Jakarta Islamic Index. The method used is regression analysis, descriptive analysis and time series data analysis.The result of the research is that inflation has a negative effect of 0.0025, the exchange rate has a positive effect on the Jakarta Islamic Index of 0.0080 and economic growth has a positive effect on the Jakarta Islamic Index of 0.0404. Abstrak. Dalam perspekti makro, investasi merupakan salah satu komponen permintaan akhir, yang menjadi indikator keseimbangan internal pada situasi keseimbangan pasar produk. Pada sisi lain, secara mikro investasi mencerminkan dunia usaha karena sumber investasi adalah dunia usaha. Perkembangan pasar modal syariah di Indonesia semakin semarak dengan lahirnya Jakarta Islamic Index (JII). Terdapat faktor yang menpengaruhi Jakarta Islamic Index yaitu variabel makro ekonomi. Tujuan penelitian ini yaitu untuk mengetahui pengaruh inflasi, nilai tukar, dan pertumbuhan ekonomi terhadap indeks harga saham Jakarta Islamic Index.Data yang digunakan dalam penelitian ini adalah data sekunder.Variabel independen nya meliputi Inflasi, Nilai Tukar, dan pertumbuhan ekonomi. Variabel dependen nya adalah Jakarta Islamic Index. Metode yang digunakan yaitu analisis regresi, analisis deskriptif dan analisis data timeseries.Hasil penelitian yaitu bahwa inflasi, berpengaruh negatif sebesar0,0025 nilai tukar berpengaruh positif terhadap Jakarta Islamic Index sebesar 0.0080 dan pertumbuhan ekonomi berpengaruh positif terhadap Jakarta Islamic Index sebesar 0.0404.